BEYOND LEGALISM: EMBRACING PROPHETIC JUSTICE IN INDONESIAS ANTI-CORRUPTION EFFORTS - Pratama, Riza Chatias; Raharjo, Trisno (Universitas Syiah Kuala, 2025)
This study explores the integration of prophetic justice into the practice of anti-corruption criminal justice in Indonesia. While significant normative and institutional progress has been made in anti-corruption law, the actual implementation often falls short of upholding substantive justice that prioritizes humanitarian values and prophetic ethics. Using a normative legal research approach grounded in the perspectives of prophetic law and social science, this study critically assesses the limitations within the judicial system that hinder the pursuit of justice that is both procedural and transformative. The findings reveal several structural obstacles, including the dominance of legal positivism, political pressures, and a lack of reflective spaces in the law enforcement process. These challenges often cause anti-corruption justice to lose its moral and spiritual dimensions. Therefore, this study underscores the necessity of both epistemological and cultural transformations within the legal framework to ensure that prophetic values, such as advocating for the marginalized, demonstrating moral courage, and fostering spiritual commitment, enhance judicial practices. Ultimately, anti-corruption justice in Indonesia must evolve beyond mere regulatory enforcement to become a dynamic and meaningful instrument of social justice, rooted in prophetic values that uphold human dignity and true equity. This study contributes significantly to the development of a humanistic and transformative legal paradigm aimed at effectively eradicating corruption.